1987
DOI: 10.1051/jphyscol:1987368
|View full text |Cite
|
Sign up to set email alerts
|

HYDROGEN EMBRITTLEMENT IN Al-Li-Cu-Mg ALLOYS (8090-T651)

Abstract: This paper describes the hydrogen embrittlement (HE) o f an A1-Li alloy aged a t 190°C and with d i f f e r e n t durations o f ageing (10, 15, 20 and 30 hr). Two techniques were employed t o measure HE : a) cathodic polarization i n a molten salts bath with-3 VIAg on tensile specimens ; b) gaseous hydrogenation on disks. Hydrogen charging was achieved a t 190°C. The results show that HE i s important when the a1 1 oy i s i n the over-aged condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…In addition to being fuel efficient, aircraft structures are also required to be corrosion resistant for long service life. In this regard, several studies have shown that AI-Li alloys are susceptible to environmental degradation (Christodoulou etal 1983;Holroyd et al 1985;Binsfield et al 1987;Meletis and Huang 1989;Balasubramaniam et a11991;Wang et al 1992). The presence of the active element Li renders the corrosion behaviour of these alloys different from the conventional A1 alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being fuel efficient, aircraft structures are also required to be corrosion resistant for long service life. In this regard, several studies have shown that AI-Li alloys are susceptible to environmental degradation (Christodoulou etal 1983;Holroyd et al 1985;Binsfield et al 1987;Meletis and Huang 1989;Balasubramaniam et a11991;Wang et al 1992). The presence of the active element Li renders the corrosion behaviour of these alloys different from the conventional A1 alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Η προσβολή των κραμάτων αλουμινίου από διάβρωση, συνδέεται κλασικά με πολύπλοκες διεργασίες οξείδωσης [57], [58], [61]. Τελευταία διαπιστώθηκε ότι επιπρόσθετα στις διεργασίες αυτές, υδρογόνο το οποίο παράγεται κατά την διάβρωση μπορεί να διαχυθεί στο εσωτερικό του μετάλλου και να οδηγήσει σε αντιδράσεις μετάλλου-υδρογόνου [52], [57], [62], [63], [64], [65], [66].…”
Section: επίδραση της διάβρωσης στην δομική ακεραιότηταunclassified